The Link between Economic Growth, Air Pollution and Health Expenditure in the G7 Countries - Zeiri, Rihem; Bouzir, Aida; Mbarek, Mohamed Hédi Benhadj; Benammou, Saloua (International Journal of Energy Economics and Policy, 2023)
The objective of this paper is to study the effect of economic growth and pollution on health expenditure in G7 countries, during the 1990-2020. In order to obtain a reliable estimate, we adopt the partial least squares (PLS) regression method, which focuses on three explanatory indicators (GDP, CO2, MR) and health expenditure (HE), as a dependent variable. The obtained empirical results reveal several important elements. First, all the models are significant, with the exception of Canada. Then, all countries have verified the economic theory that GDP positively affects HE. Then, we observe negative effects of CO2 emissions on HE, except in Japan. Finally, France, Italy, the United States and the United Kingdom have negative effects of MR on HE.